Post-pollination sepal longevity of female flower co-regulated by energy-associated multiple pathways in dioecious spinach - Ma, Xiaokai; Fatima, Mahpara; Li, Jing; Zhou, Ping; Zaynab, Madiha; Ming, Ray (Frontiers in Plant Science, 2022)
Reproductive growth is a bioenergetic process with high energy consumption. Pollination induces female flower longevity in spinach by accelerating sepal retention and development. Cellular bioenergetics involved in cellular growth is at the foundation of all developmental activities. By contrast, how pollination alter the sepal cells bioenergetics to support energy requirement and anabolic biomass accumulation for development is less well understood. To investigate pollination-induced energy-associated pathway changes in sepal tissues after pollination, we utilized RNA-sequencing to identify transcripts that were differentially expressed between unpollinated (UNP) and pollinated flower sepals at 12, 48, and 96HAP. In total, over 6756 non-redundant DEGs were identified followed by pairwise comparisons (i.e. UNP vs 12HAP, UNP vs 48HAP, and UNP vs 96HAP). KEGG enrichment showed that the central carbon metabolic pathway was significantly activated after pollination and governed by pivotal energy-associated regulation pathways such as glycolysis, the citric acid cycle, oxidative phosphorylation, photosynthesis, and pentose phosphate pathways. Co-expression networks confirmed the synergistically regulation interactions among these pathways. Gene expression changes in these pathways were not observed after fertilization at 12HAP, but started after fertilization at 48HAP, and significant changes in gene expression occurred at 96HAP when there is considerable sepal development. These results were also supported by qPCR validation. Our results suggest that multiple energy-associated pathways may play a pivotal regulatory role in post-pollination sepal longevity for developing the seed coat, and proposed an energy pathway model regulating sepal retention in spinach.